HEAT CAPACITY MEASUREMENTS OF SYNTHETIC PYROPE-GROSSULAR GARNETS BETWEEN 320 AND 1000 K BY DIFFERENTIAL SCANNING CALORIMETRY - Bosenick A.; Geiger C.A.; Cemic L. (My University, 1996)
The heat capacity of synthetic periclase (MgO), pyrope (Mg3Al2Si3O12), grossular (Ca3Al2Si3O12), and four pyrope-grossular solid solutions (Py89.8Gr10.2, Py73.6Gr26.4, Py48.8Gr51.2, Py24.0Gr76.0) has been measured between 320 and 1000 K by differential scanning calorimetry. Measurements were made in both interval-scanning and step-scanning modes; with the latter method, Cp was determined to a precision of better than +/- 1%. The results, together with previous calorimetric measurements on synthetic grossular and pyrope, now permit a complete description of the heat capacities for both phases between 10-1200 K and 10-1350 K, respectively. The following best-fit equations for the temperature range from 298 to 1200 K were obtained for pyrope and grossular, respectively (T in Kelvin and Cp in J/mol*K):Cp(pyrope) = 542.01 - 1387.07.T-0.5 - 20.492 x 106.T-2 + 2500.67 x 106.T-3;Cp(grossular) = 607.81 - 3214.49.T-0.5 - 12.141 x 106.T-2 + 1269.92 x 106.T-3 .For the solid solution garnets a model assuming ideal mixing (linear combination) of molar heat capacities of the endmember phases reproduces the experimental heat capacities within errors. This indicates that the vibrational entropies of mixing and enthalpies of mixing are temperature-independent between room temperature and 1000 K. It is expected that excess heat capacities of mixing are not present in most silicate solid solutions at temperatures between 320 and 1000 K.